Interview of Chester Segers by Brian Shoemaker and Dian O. Belanger - Segers, Chester (Byrd Polar Research Center Archival Program, 2005)
Key Individuals Mentioned Admiral Richard Byrd, pp. 1, 4, 32 Paul Siple, pp. 4, 23, 25, 27, 31-33 Spears (cook who Segers replaced), pp. 12 Paul Bloom, radio operator, pp. 14 Cliff Dickie, pp. 14-15, 38 Doc Taylor, pp. 18, 23 Moose, glaciologist, pp. 19, 23 Oz (mechanic), pp. 23 Mel (builder), pp. 23 Mr. Tuck, pp. 23, 27-28, 31 Willy Huff, pp. 23, 28 McPherson, radioman, pp. 23 Lee Remington, pp. 27 Arwal, pp. 27 Bob Benson, pp. 28 Kenny, pp. 23, 28, 38 Brown, pp. 31 Warren Hens, pp. 33 Dean Martin, pp. 34 Cathy Grant, pp. 34 Chester Segers was a cook for Operation Deepfreeze. Segers interest in the Arctic and Antarctic grew from stories he had heard involving Admiral Byrd’s Operation High Jump in 1947. He also recalled Paul Siple’s time in the Antarctic as a Boy Scout. Segers joined the Navy in 1945 at age 17 and was involved as a CBME-523 in the conflict at Pearl Harbor and Okinawa. After returning, he signed up for an operation in the Antarctic (MCB Specialty II) upon the recommendation of another cook. Segers was a Private First Class at this time. He attended Cook and Baker’s School in Newport, Rhode Island where he gained the rank of CS-1. Prior to departure, training consisted of films and 30 mile marches to get the men in physical shape for all of the walking in the Antarctic. They also met with a dietitian in Washington, D.C. to learn the proper way to cook with dehydrated foods, the use of fresh meat in the Polar Regions, and calories necessary for the activity that would be taking place. The group left in October of 1956 on the Nesplin out of Norfolk, Virginia and traveled on to Tahiti and Littleton. From Littleton the ship went on to Christchurch, New Zealand and left for the Pole on December 28, traveling through ice eight to ten feet thick. The ship docked at McMurdo Station and stayed for five to seven days. Segers traveled to the Pole on a P2V (or a R4D). Upon arrival the crew helped complete the construction of the station. Segers describes problems with altitude and the affects it had on cooking, specifically mentioning cake baking. The Minnesota Mining Company (Betty Crocker), producers of the cake mix, sent a woman up in a plane at 10,000 feet to bake a cake and then sent the results of changes necessary to Segers at the Pole. Segers was the only cook for a year, responsible for three meals per day along with preparation and cleanup, with the exception of Sunday, which was his day off. The 18 men working at the station made up a menu for each week. The mess hall was the largest room at the station so it served many purposes- movie theater, lecture hall, training room, planning session area. The scientists would also give lectures on their current work; Segers mentions Moose (a glaciologist) and the Aurora Borealis photographers. Segers discusses the officers and scientists present at the station, including Doc Taylor, Doc Siple (age 48), Lee Remington (36), Mr. Tuck, Arwal (22-the youngest of the scientists), Bob Benson. Kenny (21), and Willy Huff (30s). He also talks of the staff, such as radioman McPherson, Kenny, Moose, Oz (the mechanic) and Mel (the builder). Segers also describes the process that each man went through before being sent to the Antarctic, including psychiatric evaluation. Segers also reminisces about the sunset flag lowering ceremony and the sunrise flag raising ceremony. He discusses his observations regarding the extent of the snow cover upon exiting the buildings after the sunrise. At one point during his time at the pole, the McMurdo ice runway broke up and there were nine men stranded at the station. Segers talks about this experience and how it affected food and tobacco supplies. He also discusses the death of Admiral Byrd, how it affected the camp, Paul Siple, and the memorial service that was held, with the flag flown at half- mast. Segers then goes on to discuss the importance of the ham radio and communication with family. The radio was also used for entertainment, with Segers playing a game of gin rummy taking place in Las Vegas with Dean Martin (Segers won a trip to Las Vegas and Martin won an iceberg!). In October, the first flight into the Pole was made, but the crew had to stay for six weeks to repair the frozen engine of their P2V. Segers flew out on January 5, 1958, having spent two Christmases and two New Years at the Pole. He returned home to Rhode Island on January 20. He then went into Air Devron 6 and ran the mess hall at Christchurch every year until 1964. In January of 1961 he took the test to become galley chief. During this time, many changes took place in aviation, beginning with Globemasters, C-130s, VX-6. After his time at Christchurch, Segers went to shore duty at Quonset Point and retired in 1966. He then drove 18-wheelers for 25 years and retired in 1991. Major Topics Operation Deepfreeze Navy training and activity Activities of Paul Siple and other scientists in the Antarctic during IGY Cooking and baking in the Antarctic Funded by a grant from the National Science Foundation.